General Ordinances of the City of Aspen, §§ 183, ASPEN DAILY TIMES, Jul. 27, 1886, at 3-6 (Aspen, Colorado). - (:unkn) unknown (General Publisher, 1886)
Whenever any policeman shall make an arrest it shall be the duty of the jailer, deputy jailer, or person in charge of the city jail, to take from the person so arrested the weapon or weapons found upon him or her at the time of such arrest, and to retain the same until he, or she, or they, shall have paid whatever fine and costs, if any, there shall have been adjudged against them.
--
Keywords: PEACE OFFICERS